Complicated Benign Peptic Stricture of the Esophagus - Mulia Mulia; Jeffry Beta Tenggara; Murdani Abdullah; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2010)
Peptic esophageal stricture secondary to gastroesophageal reflux is an important cause of esophageal stenosis and dysphagia. Symptoms of peptic strictures are usually insidious but progressive beginning with dysphagia to solids followed by dysphagia to liquids. It was estimated to occur in up to 20% of untreated patients, which has decreased significantly since the era of proton pump inhibitor therapy. The presence of esophageal reflux stricture is typically diagnosed by means of a barium esophagogram, although endoscopy may have both diagnostic and therapeutic value. Treatment usually involves dilation combined with acid- suppressive therapy. We reported a 43-year-old patient with complicated benign peptic stricture of the esophagus that finally underwent esophageal resection, a rarely therapeutic option. Keywords: gastroesophageal reflux disease, benign peptic esophageal stricture, dysphagia, esophageal dilatation, surgical treatment